Analisis SWOT dengan Model Importance Performance Analysis (IPA) Pada Layanan Fintech Bank Syariah di Indonesia - Mazza Basya, Maziyah; Utami Silfia Ayu, Betty (El-Qist: Journal of Islamic Economics and Business (JIEB), 2020)
Fintech has great potential to encourage the development of Islamic economics and finance in Indonesia, especially now that fintech-based services have been widely applied in the Islamic finance industry in various countries. Fintech can be applied to Islamic banking to encourage the development of the Islamic financial industry by providing more efficiency and fast service to customers, however the existing fintech services have not fully met the expectations of its customers. Basically, SWOT analysis is used as a tool to formulate strategic planning based on the top managerial brainstorming process. Nowadays, some experts criticize the subjectivity of SWOT analysis for being too high, so this research uses the Importance Performance Analysis (IPA) method to determine the perceptions of fintech financing customers in Islamic banks in Indonesia so that it can be taken into consideration in managerial decision making for the development of Islamic bank fintech financing. in Indonesia. Key Words: Fintech; Islamic Bank; SWOT analysis; Importance Performance Analysis   Abstrak: Fintech sangat potensial untuk mendorong perkembangan ekonomi dan keuangan Syariah di Indonesia, terlebih saat ini layanan berbasis fintech telah banyak diterapkan dalam industri keuangan Syariah di berbagai Negara. Fintech dapat diaplikasikan pada perbankan Syariah untuk mendorong pengembangan industri keuangan Syariah dengan lebih memberikan efisiensi dan pelayanan jasa dalam waktu cepat kepada para nasabah, namun layanan fintech yang ada belum sepenuhnya memenuhi harapan nasabahnya. Analisis SWOT pada dasarnya digunakan sebagai alat untuk merumuskan perencanaan strategis berdasarkan proses brainstorming top manajerial. Dewasa ini, beberapa ahli mengkritisi subjektivitas analisis SWOT yang terlalu tinggi, sehingga penelitian ini menggunakan metode Importance Performance Analysis (IPA) untuk mengetahui persepsi nasabah pembiayaan fintech pada bank Syariah di Indonesia sehingga dapat dijadikan pertimbangan dalam pengambilan keputusan bagi manajerial untuk pengembangan pembiayaan fintech bank Syariah di Indonesia. Kata Kunci: Fintech; Bank Syariah; Analisis SWOT; Importance Performance Analysis